Relationship between psychological capital and nursing burnout: A systematic review and meta-analysis - Orgambidez-Ramos, Alejandro; Borrego, Yolanda; Cantero Sánchez, Fernando Miguel; León-Pérez, José M. (Wiley, 2024)
Aim: This systematic review and meta-analysis aimed to analyze studies that examinedthe relationship between psychological capital and burnout in registered nurses. Methods: This research is based on the Joanna Briggs Institute Guidelines and Preferred Reporting Items for systematic reviews and meta-analysis. A total of 180 studies on psy-chological capital and burnout were retrieved from Web of Science, Scopus, PubMed, Medline, and PsycINFO. The articles were written in English, Spanish, French, and Portuguese. Then, 23 studies were included in several meta-analyses (random-effectsmodels) performed with the R statistical program. Results: Analysis of the 23 studies revealed that psychological capital and burnoutare significantly correlated. The Psychological Capital Questionnaire (PCQ) and theMaslach Burnout Inventory (MBI) were the most used scales to measure psychologi-cal capital and burnout, respectively. The meta-analyses showed an inverse correlationbetween psychological capital and burnout (r = −0.44, 95% CI [−0.51, −0.36], n = 6092),and emotional exhaustion (r = −0.32, 95% CI [−0.42, −0.21], n = 3349). Conclusion: This review provides evidence of the negative relationship between psy-chological capital and burnout in registered nurses. Therefore, enhancing psychologicalcapital is an effective strategy to prevent and reduce burnout in nurses.Implications for nursing and health policy: Psychological capital is a personal resourceopen to development over time and susceptible to interventions aimed at promotingoptimism, efficacy, hope, and resilience. In that sense, training aimed at improvingpsychological capital, as a protective mechanism to prevent and reduce burnout andemotional exhaustion, should be considered together with organizational measures topromote nurses’ health and well-being.
Keywords: Enfermería - Estrés laboral; Burnout; Meta-analysis; Nurses; Psychological capital; Systematic review